Case Report: MOGAD - a steroid-responsive autoimmune meningoencephalitis mimicking infection - Goh, Yihui; Lye, Priscillia Pei Shi; Tambyah, Paul Anantharajah; Soon, Derek Tuck Loong; Smitasin, Nares; Ong, Jonathan Jia Yuan; Yong, Clement Hsiang Rong; Chan, Yee Cheun; Tang, David; Ng, Kay Wei Ping; Seet, Raymond Chee Seong; Quek, Amy May Lin (Frontiers in Immunology, 2025)
This case series reports three patients initially managed for presumed infectious meningoencephalitis, who were ultimately diagnosed with myelin oligodendrocyte glycoprotein associated disease (MOGAD). Their clinical presentations were strikingly similar to those of acute infectious meningoencephalitis, which posed a challenge to the initial diagnostic process. Notably, despite the absence of typical radiological changes associated with MOGAD, such as cerebral cortical encephalitis, these patients exhibited focal neurological and electroencephalographic changes. This series highlights the importance of considering MOG antibody testing in cases of aseptic meningoencephalitis, where early and accurate diagnosis can influence treatment decisions and patient outcomes in this steroid-responsive condition.